INTERFERENSI MORFOLOGIS BAHASA JAWA KE DALAM BAHASA INDONESIA PADA TUTURAN GURU DAN SISWA DALAM KEGIATAN PEMBELAJARAN BAHASA INDONESIA KELAS XI MA AL MISRI CURAHMALANG RAMBIPUJI JEMBER - Azizah, Nuril; Parto, Parto; Widjajanti, Anita (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Jember, 2022)
Morphological interference is the inclusion of elements of the formation of a language into another language. Morphological interference can occur in spoken or written language. One of them is in the speech of teachers and students in Indonesian language learning activities in 11th grade of MA Al Misri Curahmalang Rambipuji Jember. The purpose of this study was to describe the forms and factors of the occurrence of morphological interference from Javanese into Indonesian in the speech of teachers and students in Indonesian language learning activities in class XI MA Al Misri Curahmalang Rambipuji Jember. The design and type of research are descriptive qualitative. The data in this study were word indicated morphological interference, answers from interviews, and questionnaire answers. The data sources in the study include teacher and student speech in learning activities, transcripts of interviews, and questionnaire. The data-gathering techniques of this study use observation, questionnaire, and interview techniques. Data analysis in this study includes data reduction, data presentation, and writing conclusion. Based on the results and discussion, there are two forms of morphological interference, namely affixation interference, and reduplication interference. There are two factors that cause morphological interference in teacher speech and there are five factors that cause morphological interference in student speech. Keyword: Morphological interference, affixation interference, interference reduplication, factors causing the interference morphological